Hydrogenation kinetics of halogenated nitroaromatics over Pt/C in a continuous Micro-packed bed reactor. (6th April 2022) - Duan, Xiaonan; Yin, Jiabin; Huang, Mengmeng; Wang, Peixia; Zhang, Jisong
Highlights: The kinetic model of the hydrogenation of halogenated nitrobenzene was established. Kinetic parameters including activation energies and rate constants were obtained successfully. Kinetic model fitted well with the experimental value and the influence of hydrogen pressure was also investigated. Abstract: Halogenated aromatic anilines are series of crucial intermediates for the synthesis of pigments, medicines and pesticides in the fine chemistry. However, efficient inhibition of undesired dehalogenation is difficult to achieve in the commonly used batch reactors. Although employing continuous flow technology and modified catalysts could alleviate dehalogenation, obtaining high selectivity of halogenated aromatic anilines especially for brominated aromatic amines and iodine aromatic amines is still challenging. In this study, a continuous flow system based on micro-packed bed reactor was developed and a kinetic model of the hydrogenation of halogenated nitrobenzene was established. Kinetic parameters for the reductions of p -chloronitrobenzene, p -bromonitrobenzene and p -iodonitrobenzene were acquired and the kinetic model exhibited good fit for the transformation of each substance. Moreover, the accuracy of kinetic model was validated by the comparison with the values in literature. The obtained kinetic model offered helpful information for the process optimization of hydrogenation of halogenated nitroaromatics in continuous flow system.